ANALISIS KEBERLANJUTAN USAHA SAYURAN HIDROPONIK PADA MASA PANDEMI COVID-19 DI KOTA MAKASSAR (STUDI KASUS DI GREEN TOP FARM) - Nur Indah Waliyanti; Jusni Jusni; Pipi Diansari (Universitas Galuh, 2022)
Vegetable commodities have an important role to meet human needs, especially in terms of adequate food and nutrition. Vegetables can be produced in several media and one of the planting methods is hydroponics. Makassar City during the Covid-19 pandemic, many people consumed vegetables, especially hydroponics because of public awareness of health in the midst of this outbreak. One of the hydroponic vegetable businesses in Makassar City is Green Top Farm. This study aims to analyze the sustainability of the vegetable business at Green Top Farm during the covid-19 pandemic. This research method uses quantitative descriptive analysis using sustainability indicators. Determination of the research location is done intentionally (purposive). The data used is primary data. The sustainability of Green Top Farm's hydroponic vegetable business is divided into four aspects, namely economic aspects, social aspects, environmental aspects and technological aspects. The results show that business sustainability in the economic aspect gets a value of 7 which is included in the high sustainability category, business sustainability in the social aspect gets a value of 6 which is included in the moderate sustainability category, business sustainability in the environmental aspect gets a value of 7 which is included in the low sustainability category. high and business sustainability in the technology aspect gets a score of 6 which is included in the moderate sustainability category. These four aspects can be said that this effort can be continued well.